ВОПРОСЫ СОТРУДНИЧЕСТВА СЕМЬИ И МАХАЛЛИ В СИСТЕМЕ НОВОЙ МОЛОДЕЖНОЙ ПОЛИТИКИ УЗБЕКИСТАНА (Scientific journal of the Fergana State University, 2023)
In the article, from the beginning of the new period of development of Uzbekistan to the present day, a wide range of reforms in the field of Youth Policy, their directions, improvement of legal foundations, as well as the modern state of family-neighborhood cooperation in solving youth problems have been studied.